2020
DOI: 10.7759/cureus.6583
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided Platelet-rich Plasma Application Versus Corticosteroid Injections for the Treatment of Greater Trochanteric Pain Syndrome: A Prospective Controlled Randomized Comparative Clinical Study

Abstract: The purpose of this clinical study was to evaluate and compare the effectiveness of ultrasound (US)-guided platelet-rich plasma (PRP) injections versus US-guided corticosteroid injections (CSI) in the treatment of greater trochanteric pain syndrome (GTPS). Methods Between January 2015 and December 2016, 24 patients with GTPS were enrolled and randomized in two groups (A and B). Group A (study group) patients received US-guided PRP injection treatment, while group B (control group) patients received US-guided C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In recent years, the efficacy of PRP injection vs corticosteroid injection in the treatment of a variety of musculoskeletal disorders including plantar fasciitis, [ 34 ] elbow epicondylitis, [ 35 ] knee osteoarthritis, [ 36 ] greater trochanteric pain syndrome, [ 37 ] and rotator cuff lesions [ 38 ] has been compared. Nevertheless, the efficacy of PRP injection vs corticosteroid injection as a conservative treatment for rotator cuff lesions remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the efficacy of PRP injection vs corticosteroid injection in the treatment of a variety of musculoskeletal disorders including plantar fasciitis, [ 34 ] elbow epicondylitis, [ 35 ] knee osteoarthritis, [ 36 ] greater trochanteric pain syndrome, [ 37 ] and rotator cuff lesions [ 38 ] has been compared. Nevertheless, the efficacy of PRP injection vs corticosteroid injection as a conservative treatment for rotator cuff lesions remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized clinical trial of 24 patients with GTPS compared PRP injections with CSI over a 2-year follow-up period. 53 At 1 month, the CSI group showed significantly greater improvement in pain and function than the PRP group, with HHS improvements of 33 and 25 points, respectively ( p < 0.05), and VAS score improvements of 4.6 and 2.6 points, respectively ( p < 0.05), compared with the pre-injection baseline scores. However, at 2-year follow-up, patients who received a CSI returned to their pre-injection HHS and VAS scores, whereas the PRP group experienced sustained improvements of 40 and 5.7 points, respectively ( p < 0.05 for both).…”
Section: Nonoperative Managementmentioning
confidence: 82%
“…Due to case report [ 22 ], duplicate [ 23 ], no required data [ 24 – 27 ], and study design [ 28 30 ], 9 studies were excluded. Finally, 8 RCTs [ 31 38 ]were included in our meta-analysis, which included a total of 764 participants. The study flowchart is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%